The Influence of Implementing Government Accounting Standards, Government Internal Control Systems, Utilization of Information Technology and Apparatus Competence on the Quality of West Java Provincial Government Financial Reports - Sunarya, Asep; Intan Mauludina; Silviana (International Journal of Social Science and Business, 2024)
This study aims to analyze the effect of the application of government accounting standards, government internal control systems, the use of information technology, and the ability of apparatus on the quality of the financial statements of the West Java Provincial Government. The population of this study consists of offices and agencies in the Regional Apparatus Organization (OPD) in the West Java Provincial Government, totaling 38 agencies. This study used primary data obtained through the distribution of questionnaires to the compilers of the financial statements of each OPD. The research sample consisted of 38 respondents representing the OPD. The analysis method used is multiple linear regression analysis using the Statistical Product and Service Solutions (SPSS) program version 26. The results showed that together, the application of government accounting standards, government internal control systems, the use of information technology, and apparatus capabilities had a significant effect on the quality of the West Java Provincial Government's financial statements, with a significance value of 0.000. This study concludes that the application of government accounting standards, government internal control systems, the use of information technology, and the ability of apparatus have an important role in improving the quality of financial statements. The implication of this study is the importance of the West Java Provincial Government to pay attention to and improve these aspects to improve transparency, accountability, and the quality of financial statements.